PERBANDINGAN TINGKAT PENGETAHUAN PERMAINAN TRADISIONAL PADA SISWA KECANDUAN GADGET DAN TIDAK KECANDUAN GADGET - Aluwis, Aluwis; Manurizal, Manurizal; Supriyadi (Jurnal Muara Pendidikan, 2024)
The problem in this study was that gadget addiction makes children less interested in playing traditional games, so students did not recognize these games. The purpose of this study was to compare the level of knowledge of traditional games among students addicted to gadgets and those not addicted to gadgets in the upper grades of SDIT Robbani Hutaraja Tinggi Sub-District. This research used qualitative descriptive methods to compare the two variables. The population in this study were upper-grade students of SD IT Robbani, Hutaraja Tinggi Sub-District, with a Purposive Sampling technique, namely 30 students addicted to gadgets and 30 not addicted to gadgets. The technique used for taking tests in this study was distributing questionnaires. In this study, the data analysis used was homogeneity analysis, and hypothesis testing was performed using the t-independent test. Conclusion Comparison of the Level of Knowledge of Traditional Games in Gadget Addicted Students and not Addicted to Gadgets in upper-grade SDIT Robbani Hutaraja Tinggi District which is carried out statistical calculations by the formula used (t-test) obtained tcount 2.029 and ttable 1.699 which means tcount> ttable, means Ho is rejected and Ha is accepted. Thus, there is a comparison of the level of knowledge of traditional games in students addicted to gadgets and those not addicted to gadgets in the high-grade of SDIT Robbani Hutaraja Tinggi District